DEVELOPMENT POLICIES AND PARTNERSHIPS IN SOUTHERN EUROPE: EVIDENCE FROM VARNA AND BARI - Theodore Metaxas (Revista Galega de Economía, 2015)
The aim of this research is to investigate through empirical and primary data thepossibility of design and implementation of development policies and partnerships in the SouthEastern Europe especially in the areas of Bari and Varna. Specifically, this research is based ondata extracted from 183 SMEs firms of all the productive sectors which express their evaluationsfor the role of specific development policies to their competitiveness per sector but also thedegree and dynamic of developing partnerships with the local and regional authorities. Further thefindings of the analysis designate the important issues of regional economic development focusingon the ability of public authorities to design and implement effectively development policies inorder to benefit the competitiveness of themselves and the firms as well as the special sensitiveareas of Southeastern Europe which is a very interesting zone for research.